2000
DOI: 10.1002/jor.1100180206
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of elbow joint kinematics in passive motion by electromagnetic motion tracking

Abstract: Summary:This research provides a detailed analysis of the kinematics of passive elbow motion. I1 quantifies how closely humeroulnar kinematics approximates rotation around a fixed axis. The results are clinically relevant for emerging treatment modalities that impose an artificial hinge to the elbow joint, such as total elbow arthroplasty and articulated external fixation. In a cadaveric study of seven specimens. we quantified ulnar rotation around the humerus in terms of instantaneous screw displacement axes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
55
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 13 publications
6
55
0
Order By: Relevance
“…8 In particular, the helical axis, also known as Screw Displacement Axis (SDA), method has been widely reported in the biomechanics literature and shown to accurately determine the true elbow flexion axis. [9][10][11][12] It has also been shown that the SDA method can be used to calculate the forearm rotation axis, and that it intersects with the flexion axis SDA at the radiocapitellar joint. 12 This provides a convenient way to locate the origin of a CS, and we theorized that these characteristics could be used to create CS based on motion of the upper extremity, hereafter referred to as Motion-Derived CS.…”
mentioning
confidence: 99%
“…8 In particular, the helical axis, also known as Screw Displacement Axis (SDA), method has been widely reported in the biomechanics literature and shown to accurately determine the true elbow flexion axis. [9][10][11][12] It has also been shown that the SDA method can be used to calculate the forearm rotation axis, and that it intersects with the flexion axis SDA at the radiocapitellar joint. 12 This provides a convenient way to locate the origin of a CS, and we theorized that these characteristics could be used to create CS based on motion of the upper extremity, hereafter referred to as Motion-Derived CS.…”
mentioning
confidence: 99%
“…The elbow brace may interfere with normal screw displacement as well as valgus/varus movement of the elbow joint. Bottlang et al 7) stated that the screw displacement axis varied over a relatively small range. For practical purposes, wearing an elbow brace protects the collateral ligament as well as the osteochondral graft from excess stress during rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…The passive mechanism provides A FE with three passive DOFs, which allow the NEUROExos axis to trace the same double conic frustum traced by the human axis (Bottlang et al, 1998;Bottlang et al, 2000;Duck et al, 2003). First, A FE can rotate in the frontal plane of an angle γ f = ±15°.…”
Section: -Dof Passive Mechanismmentioning
confidence: 99%